(untitled) (Global Journal of Management and Business Research, 2018)
needed for economic growth and bridging the gap between savings and investment in Nigeria. This study investigates the effects of exchange rate volatility on foreign portfolio investment in Nigeria. The effects of volatility of exchange rate on foreign portfolio investment inflows to Nigeria were captured through the official exchange rate and bureau-de change rate. A monthly time series data were sourced from Central Bank of Nigeria covering a period of 10years from 2007-2016.This study employed General Autoregressive Conditional Heteroskedasticity GARCH (1,1) model to test for volatility in both official and BDC rate. A twostage least square (TSLS) method was used to test the relationship between the volatility and foreign portfolio investment in Nigeria. The results revealed that volatility in the official rate exerted positive significant impact of 8.119872 on foreign portfolio investment inflow into Nigeria, while the BDC volatility showed a negative significant impact of -5.961654 on foreign portfolio investment inflow into Nigeria within the study period. The study concluded that the official exchange rate volatility has a significant and positive effect on foreign portfolio investment in Nigeria, while the bureau-de change volatility has a significant and negative relationship with foreign portfolio investment in Nigeria. Hence, the study recommended that monetary authority should formulate such policies that will stabilize exchange rate so as to boost the investors’ confidence.